Bright Light Therapy and Circadian Cycles in Institutionalized Elders - Rubiño, José A.; Gamundí, Antoni; Akaarir, Mourad; Canellas, Francesca; Rial, Rubén; Nicolau, M. Cristina (Frontiers in Neuroscience, 2020)
Bright light therapy has been found to be an efficient method to improve the main parameters of circadian rhythms. However, institutionalized elders may suffer reduced exposure to diurnal light, which may impair their circadian rhythms, cognitive performance and general health status. To analyze the effects of 5 days of morning exposure for 90 min to bright light therapy applied to institutionalized elderly people with mild/moderate cognitive impairment. 37 institutionalized subjects of both sexes, aged 70-93 years. The study lasted three consecutive weeks. During the second week the subjects were submitted to bright light therapy (7000-10000 lux at eye level) on a daily basis. Cognition, attention and sleep quality were evaluated at the beginning of the first and third week. Circadian variables were recorded continuously throughout the three weeks. Non-invasive holders and validated tests were used to analyze the variables studied. Application of bright light therapy caused significant improvements in general cognitive capabilities, sleep quality and in the main parameters of the subject’s circadian rhythms. We hypothesize these effects were the result of activating the residual activity of their presumably weakened circadian system. Conclusions: The results show that merely 90 min of bright light therapy for five days is enough to achieve a significant improvement in a constellation of circadian, sleep, health and cognitive factors. In short, bright light therapy is an affordable, effective, fast-acting therapy for age-related disturbances, with many advantages over pharmacological alternatives.